IFAD Proving the poor are bankable - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
There is no denying that credit is essential to most agricultural and rural development activities. Whether as cash or in kind, credit provides a strong incentive as well as practical assistance for small farmers considering the adoption of new...